Monitoring the environmental evolution and its relationship with anthropogenic activities using magnetic and geochemical proxies on Lake Melincué sediments. (June 2022) - Achaga, R.; Gogorza, C.; Irurzun, M.A.; Goguitchaichvili, A.; Mestelán, S.; Ruiz Fernández, A.C.; Sánchez Cabeza, J.A.; Sánchez Bettucci, L.; Sinito, A.; Morales, J.; Martínez, D.
Abstract: Two sediment cores, collected from the center of the Lake Melincué (Santa Fe, Argentina), were analyzed using rock magnetic results, element composition, Total Organic and Inorganic Carbon (TOC and TIC) and Total Nitrogen (TN) to reconstruct the environmental variations in the last three centuries, associated with climatic changes and/or human activities. 210 Pb dating, chronostratigraphic markers, and paleomagnetic results were used to create the age model of the cores. Rock magnetic analyses suggest that (titano)magnetite and a low proportion of hematite are the main magnetic phases. In addition, geochemical results compared with rock magnetic analysis indicate the possible presence of diagenetic dissolution. Four well-differentiated environmental phases were found with variations from cold to more humid and warmer environmental conditions. Unit 0 from 1750 CE to 1783 CE with a cold environment and high lake level, Unit 1 from 1783 CE to 1878 CE with continuing cold environmental conditions but a low lake level, showing the end of the Little Ice Age (LIA) toward the top, Unit 2 from 1878 CE to 1874 CE with a wetter environment and Unit 3 from 1974 CE to 2016 CE with wet and warm conditions and a high lake level. Highlights: We report new paleoclimatic multiproxy results in Lake Melincue, Argentina. The age model was validated by stratigraphic markers and Paleosecular Variations. Four environmental scenarios were distinguished from dry to wet conditions. The results are related to the anthropogenic activity (land use and fertilizers).